2020
DOI: 10.1017/s000711452000207x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of household cooking salt and eating out on iodine status of pregnant women in environmental iodine-deficient coastal areas of China

Abstract: As city residents eat out more frequently, it is unknown that if iodised salt is still required in home cooking. We analysed the relationship of household salt and eating out on urinary iodine concentration (UIC) in pregnant women. A household condiment weighing method was implemented to collect salt data for a week. A household salt sample was collected. A urine sample was taken at the end of the week. Totally, 4640 participants were investigated. The median UIC was 139·1 μg/l in pregnant women and 148·7, 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…We obtained the data from a pregnant study conducted in Shanghai, China from April to October 2017 [25]. The Ethical Committee of the Shanghai Center for Disease Control and Prevention approved the study (No.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained the data from a pregnant study conducted in Shanghai, China from April to October 2017 [25]. The Ethical Committee of the Shanghai Center for Disease Control and Prevention approved the study (No.…”
Section: Methodsmentioning
confidence: 99%
“…The present data was from a prospective birth cohort focusing on iodine nutritional status of pregnant women, thyroid function and the growth and development of their offspring in Shanghai, China, from April to October, 2017. A detailed description of the cohort is given in a previous paper [17]. This study was approved by the Ethical Committee of the Shanghai Center for Disease Control and Prevention (No.…”
Section: Methodsmentioning
confidence: 99%
“…Although eating out has been associated with higher total energy and macronutrient intakes including fat, it is unclear if it may increase the consumption of iodine intake. This is because it depends on several factors including the frequency of eating out, the amount of iodised salt added during cooking and at the table . In Shanghai, the usage rates of iodised salt and qualifiediodised salt reported by the authors indicated a low coverage of iodised salt (< 90 %) (1)(2)(3) . In addition, only a small percentage of pregnant women (11•3 %) reported the use of iodine supplements (1) .…”
mentioning
confidence: 95%
“…In Shanghai, the usage rates of iodised salt and qualified-iodised salt reported by the authors indicated a low coverage of iodised salt (< 90 %) (13) . In addition, only a small percentage of pregnant women (11·3 %) reported the use of iodine supplements (1) .…”
mentioning
confidence: 97%
See 1 more Smart Citation